Open Geotechnology in the development of non-metallic mineral resources during road construction - Margiev E.A., Kortiev L.I., Kortiev A.L., Dryaev A.A,; R.P., Kulumbegov (Opción, 2019)
The study aims to investigate open geotechnology in the development of non-metallic mineral resources during road construction and its R&D support via comparative qualitative research methods. As a result, the broadening of the road causes the rocks to slide, causing dangerous traffic conditions, and the transition to the tunnel version increases the cost to an unthinkable amount. In conclusion, for the purpose of longevity and road safety, the design and construction of roads in mountainous conditions should be accompanied by scientific and technical expertise conducted by research organizations on traffic safety.